2011
DOI: 10.1097/mou.0b013e3283455a21
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted laparoscopic prostatectomy: a critical analysis of its impact on urinary continence

Abstract: Much progress has been achieved in elucidating the anatomic, physiologic, and neural basis of the male continence mechanism, resulting in novel adaptations of the conventional approach to radical prostatectomy with the aim of preserving continence and accelerating its return. Various principles for augmenting continence return have been proposed which have been evaluated in series of open, laparoscopic, and robotic-assisted radical prostatectomy. Going forward, we foresee a paradigm shift from individual techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…In fact, other investigators have demonstrated improved continence outcomes with better nerve sparing, suggesting the role of periprostatic nerves in urinary as well as sexual function. [31][32][33] The positive surgical margin rate between the groups was not significantly different, suggesting that alteration of technique based on real-time penile oxygen monitoring did not compromise oncologic outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, other investigators have demonstrated improved continence outcomes with better nerve sparing, suggesting the role of periprostatic nerves in urinary as well as sexual function. [31][32][33] The positive surgical margin rate between the groups was not significantly different, suggesting that alteration of technique based on real-time penile oxygen monitoring did not compromise oncologic outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…The magnification of 10 to 20 times, the excellent degrees of freedom for movement of the instruments and the intuitive handling of the machine are advantages compared with the open or standard laparoscopic approaches (7,27,33,36). Although evidence for better oncological and functional results are still unproven robotic assisted radical prostatectomy (1,3,15,21,26,39) is in many countries now the standard of care for the surgical removal of the prostate (4,6,22).…”
Section: Resultsmentioning
confidence: 99%
“…The magnification of 10 to 20 times, the excellent degrees of freedom for movement of the instruments and the intuitive handling of the machine are advantages compared with the open or standard laparoscopic approaches (7,27,33,36). Although evidence for better oncological and functional results are still unproven robotic assisted radical prostatectomy (1,3,15,21,26,39) is in many countries now the standard of care for the surgical removal of the prostate (4,6,22).…”
Section: Resultsmentioning
confidence: 99%